Signs of Nervous System Sensitization in Female Runners with Chronic Patellofemoral Pain - Brian J. Eckenrode; David M. Kietrys; Allison Brown; J. Scott Parrott; Brian Noehren (North American Sports Medicine Institute, 2023)
# Background Patellofemoral pain (PFP) is a common overuse injury among runners, affecting females at a higher rate than males. PFP can often become chronic, with evidence suggesting it may be linked to both peripheral and central sensitization of the nervous system. Sensitization of the nervous system can be identified through quantitative sensory testing (QST). # Hypothesis/Purpose The primary objective of this pilot study was to quantify and compare pain sensitivity as identified through QST measures, in active female runners with and without PFP. # Study Design Cohort Study # Methods Twenty healthy female runners and 17 female runners with chronic PFP symptoms were enrolled. Subjects completed the Knee injury and Osteoarthritis Outcome Score for Patellofemoral Pain (KOOS-PF), University of Wisconsin Running Injury and Recovery Index (UWRI), and the Brief Pain Inventory (BPI). QST consisted of pressure pain threshold testing to three local and three distant sites to the knee, heat temporal summation, heat pain threshold, and conditioned pain modulation. Data was analyzed utilizing independent t-tests for comparison of between-group data, effect sizes for QST measures (Pearson's r), and Pearson's correlation coefficient between pressure pain threshold values at the knee and functional testing. # Results The PFP group exhibited significantly lower scores on the KOOS-PF (p\<0.001), BPI Pain Severity and Interference Scores (p\<0.001), and UWRI (p\<0.001). Primary hyperalgesia, identified through decreased pressure pain threshold at the knee, was detected in the PFP group at the central patella (p\<0.001), lateral patellar retinaculum (p=0.003), and patellar tendon (p=0.006). Secondary hyperalgesia, a sign of central sensitization, was observed via differences in pressure pain threshold testing for the PFP group at the uninvolved knee (p=0.012 to p=0.042), involved extremity remote sites (p=0.001 to p=0.006), and uninvolved extremity remote sites (p=0.013 to p=0.021). # Conclusion Compared to healthy controls, female runners with chronic PFP symptoms exhibit signs of both peripheral sensitization. Despite actively participating in running, nervous system sensitization may contribute to continued pain in these individuals. For female runners with chronic PFP, physical therapy management may need to include interventions which address signs of central and peripheral sensitization. # Level of Evidence Level 3